Effect of Spice Mixtures on Performance and Economics of Broiler Chicken: - D. Tewari; Chakara, Sonu Kumar (Indian Journal of Animal Nutrition, 2023)
To investigate the effect of spice mixture (turmeric, fenugreek, cinnamon, cumin and ajwain) on the performance and economics 250 broiler chicks (Vencobb-400Y) were randomly distributed into five dietary treatment groups- basal diet without supplement (NCG) or with antibiotic (PCG), spice mixture at 0.5% (SMG-0.5), spice mixture at 1.0% (SMG-1.0) and spice mixture at 1.5% (SMG-1.5) levels for five week. The effect of spice mixture on body weight gain, feed intake, feed conversion ratio, production indices and economics was assessed. After five weeks experiment, body weight gain in all SMG groups as well as PCG group had significantly (P<0.05) higher than NCG group. The feed intake of PCG group was significantly lower than other treatment groups except SMG-1.5. FCR value of NCG group was significantly (P<0.05) higher than PCG and SMG-1.5 while similar to SMG-0.5 and SMG-1.0 group birds. The nutrient retention was comparable among groups. The net profit per bird of NCG and SMG groups was significantly (P<0.05) lower from PCG birds. It can be concluded that spice mixture at 1.5% level improved performance indices, FCR and economics of broilers and can be used as an alternative of AGPs for broilers ration.